2021
DOI: 10.1111/evo.14366
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for short‐term evolutionary response to a warming environment in Drosophila

Abstract: Adaptive evolution is key in mediating responses to global warming and may sometimes be the only solution for species to survive. Such evolution will expectedly lead to changes in the populations' thermal reaction norm and improve their ability to cope with stressful conditions. Conversely, evolutionary constraints might limit the adaptive response. Here, we test these expectations by performing a real-time evolution experiment in historically differentiated Drosophila subobscura populations. We address the ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 95 publications
1
7
0
Order By: Relevance
“…It is important to note that the adaptive responses we observe were only obtained after the thermal increase per generation in the warming cycle was halted by generation 24 (Santos et al 2021c(Santos et al , 2023a. This finding is in agreement with those of another evolution experiment addressing adaptation to incremental warming in seed beetles (Hallsson and Björklund 2012;Rogell et al 2014).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to note that the adaptive responses we observe were only obtained after the thermal increase per generation in the warming cycle was halted by generation 24 (Santos et al 2021c(Santos et al , 2023a. This finding is in agreement with those of another evolution experiment addressing adaptation to incremental warming in seed beetles (Hallsson and Björklund 2012;Rogell et al 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Our team has been studying how populations of this species evolve under an increasingly warmer environment (Santos et al 2021c). We have been focusing on populations from northern (high latitude) and southern (low latitude) European locations to address the relevance of different historical backgrounds during thermal evolution (Santos et al 2021c). The thermal setting in the warming regime was incremental (0.2ºC per generation) until generation 24 and then the thermal environment was kept constant across generations until the last assay, with a daily fluctuating regime spanning both high and low temperatures (with daily peaks of respectively 11ºC and 5ºC above and below 18ºC, the control conditions).…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, heat tolerance evolution had positive consequences on fitness-related traits, including increased fecundity and preadult survival. Despite some evidence showing that upper thermal limit (CTmax) had limited evolutionary potential (Kellermann et al 2012;Kelly et al 2012), our research group has found that CTmax of D. subobscura populations have enough genetic variation (Castañeda et al 2019), to adapt to local conditions (Castañeda et al 2015) and respond to artificial selection (Mesas et al 2021; but see Santos et al 2022 for no evolutionary response to warm temperatures). Thus, heat tolerance can evolve under different thermal scenarios but with different outcomes on associated traits depending on the intensity of thermal stress.…”
Section: Discussionmentioning
confidence: 95%
“…populations lead to the expectation that evolution will be able to keep pace with climate change (Harshman & Hoffmann, 2000). Yet this expectation is contrasted against field and laboratory experimental evolution studies showing limited evolutionary responses under warming (Santos et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there are exceptions, as shown in the field transplant study in Arabidopsis (characterized by a short generation time) demonstrating evolutionary lags in climate adaptation (Wilczek et al, 2014). Indeed, such methodological differences could be especially important to consider, as laboratory experimental evolution studies proffer a somewhat more optimistic view of the ability of Drosophila to keep pace with climate change (Harshman & Hoffmann, 2000) than field studies (Rezende et al, 2020; Santos et al, 2021). Further still, it is difficult to reconcile both of these Drosophila studies that provide evidence for some potential lags with field‐derived evidence of rapid seasonal adaptation in this group (Rudman et al, 2022).…”
Section: The Evidence For Keeping Pacementioning
confidence: 99%